Arbuscular Mycorrhiza in Highly Fertilized Maize Cultures Alleviates Short-Term Drought Effects but Does Not Improve Fodder Yield and Quality - Polcyn, Władysław; Paluch-Lubawa, Ewelina; Lehmann, Teresa; Mikuła, Robert (Frontiers in Plant Science, 2019)
Under fertilization levels specific to intensive farming, the impact of compensation of soil nutritional value by arbuscular mycorrhiza (AM) might be limited. Therefore, the question arises whether modern crop varieties, selected for high NPK assimilation rate, are able to gain symbiotic benefits under other challenging field conditions, such as drought. Accordingly, in this study we aimed to evaluate the contribution of Rhizophagus irregularis to the drought response of a stay-green corn hybrid in pot cultures equally fertilized until silking, compared to non-mycorrhizal (NM) counterparts. The highest tested fertilization regime not detrimental to the long-term vitality of intraradical hyphae reached the levels recommended for field cultivation of silage corn, except phosphorus application restricted to 60%. Under normal watering, mycorrhiza increased leaf nitrogen and phosphorus acquisition but only in cultures supplied with low NPK levels. At high fertilization levels, only the older leaves retained AM dependency, whereas for other leaf positions the AM-NM differences were levelled out. The similar size and nutritional status of highly fertilized AM and NM cultures, used in this study, eliminated fungal benefits before and during the two-week drought progression. Nevertheless, mycorrhizal contribution became evident at the time of renewed watering, when AM plants showed much faster reversal of drought-induced leaf senescence symptoms: impaired photosynthesis and nitrogen management. Our results suggest that mycorrhiza can alter drought-induced senescence even in stay-green mutants. Moreover, this effect was apparently not mediated by AM-improved growth but triggered by activation of fungal transport at the time of recovery. Interestingly, the fungal protective potential was shown to be preserved at the expense of lowering AM vesicle number. It can be interpreted as engagement of hyphal nutritional resources targeted to maintain the symbiotic relationship despite the reduced vitality of the host. Finally, we compared the productivity of AM and NM cultures subjected to short-term drought at silking time and further fertilized with moderate or high NPK doses until the grain-filling stage. The yield and nutritive value of green forage showed that alleviation of drought-induced senescence by AM was not sufficient to have a significant positive effect on the final productivity of NM plants.